Steeple, Volume 2, The silvery moon - Allison, John, 1976- (Dark Horse Comics,U.S, 2021)
Former curate Billie has moved on to a new path...as a priestess in the Church of Satan. Meanwhile, her friend Maggie has made a similar switch--from Satanist to church-bound do-gooder. But when the light of the supermoon turns a Church of Satan warlock into an almost-werewolf, Billie's well-meaning solutions bring her evil boss to the breaking point, just as Maggie's chaotic nature begins to wear thin on her Godly supervisors. Then, when a mysterious visitor is found in a cave, an ancient evil from the unknowable depths of the Pacific Ocean is hot on their heels...and so is Christmas! In the midst of the madness, Billie does her best to arrange an improbable Saturnalia truce between the churches of England and Satan. --